PENGARUH LIKUIDITAS TERHADAP RETURN ON ASSET DENGAN FIRM SIZE SEBAGAI VARIABEL MODERASI PADA PERUSAHAAN SUBSEKTOR KOSMETIK DAN PERALATAN RUMAH TANGGA YANG TERDAFTAR DI BURSA EFEK INDONESIA - Putra Akbar, Ade; Jumady, Edy; Heslina, Heslina (Jurnal Bina Bangsa Ekonomika, 2025)
Ade Putra Akbar (2022 456 43 1334). The Effect of Liquidity on Return on Asset with Firm Size as a Moderating Variable in Cosmetics and Household Appliances Subsector Companies Listed on the Indonesia Stock Exchange. Guided by Edy Jumady and Heslina. Cosmetics and household goods companies are one of the consumer goods industry subsector companies listed on the Indonesia Stock Exchange that are engaged in the production of food and beverages, body care products, cosmetic products, traditional medicine products (herbal medicine), fragrance products, hair care products, and home care products. The increasing business competition in the era of globalization makes companies have to adjust and must be able to read the situation in order to manage the company well and improve performance so that the company's goals can be achieved. The method used in this study is an explanatory method with a quantitative research approach and secondary data sources. The data analysis obtained in this study will use a statistical data processing program known as Eviews Software version 12. Panel Data Regression Estimation Method There are three models that can be used, namely the Common Effect Model (CEM), Fixed Effect Model (FEM), and Random Effect Model (REM). Based on the results of the study, the results of statistical testing through eviews-12 software can be concluded that the Current Ratio has a negative and significant effect on Return on Assets. The results of statistical testing so that it can be concluded that Firm Size has a negative and significant effect on Return on Asset. The results of statistical testing so that it can be concluded that the moderation of Firm Size between Current Ratio (CR) and Return on Asset (ROA) has a positive and significant relationship.